The implementation of m-commerce in the Sultanate of Oman: trends and issues - Sadi, A.H.M. Saifullah; Azad, Imran; Noordin, Mohamad Fauzan (2008)
Mobile commerce is an emerging discipline that involves mobile device, wireless networks and Internet technologies. The Sultanate of Oman is one of the fastest growing telecoms nations in Asia and especially among the Arab Countries. The aims of this paper is to investigate the level of adoption of Information and Communications Technology (ICT) in the banking sector and investigates the prospects of M-Commerce in Oman based on Strengths, Weaknesses, Opportunities and Threats (SWOT) analysis. The findings shows that most of the banks and the telecoms operators have the strengths to offer better qualities of electronic and mobile services to the residents of Oman. Currently, the banks are trying to offer one form of M-Banking or the other, but the weaknesses are the level of patronage and fewer services. The level of patronage is low and it requires concerted efforts of the telecoms operators and the financial institutions to fast-track the development of M-Banking services to the people. It is expected that recent development of 3G (Third Generation) network will boost M-Commerce activities in the sultanate of Oman but may require further investment in the quality of cell phones and mobile network.